The Female Impact: Gendered Effects on Congressional Behavior Over Time. - Weissman, Anna S. (Tufts Archival Research Center, 2017)
Abstract: As a nation, we stand far behind other progressive forces on the issue of gender equality, particularly in politics, where representatives’ genders do not accurately reflect the gender makeup of our country. Thirty years ago around 7% of the House and 2% of the Senate were comprised of women. Today approximately 20% of the entire Congress consists of women. The gender divide has decreased, but there is still an extremely evident gap. The purpose of my research was to answer the following question: How, if at all, has the increasing number of women in the US Congress over the past 25 years influenced the behavior of its members? In order to answer this question, I quantitatively analyzed gendered volubility in the Congressional chamber and the effectiveness of sponsorship and cosponsorship over time, while accounting for other demographic factors as well. I performed qualitative interviews on gendered legislative behavior with politicians and staffers involved in the legislative process. My most striking results suggest that the number of women in Congress does not necessarily have a significant impact on women’s behavior, but it does influence the behavior of Congressmen.